Pengaruh Kompensasi Finansial Dan Kepuasan Kerja Terhadap Turnover Intention Karyawan Bank Sumsel Babel Kantor Pusat - Andari, Mayang Rizky; Siregar, Lina Dameria; Farla, Wita (Politeknik Negeri Ambon, 2024)
To study aims to: (1) To determine and analyze the effect of financial compensation on turnover intention of Bank Sumsel Babel Head Office Employees,(2) To determine and analyze the effect of job satisfaction on turnover intention of Bank Sumsel Babel Head Office Employees. The research was conducted on Bank Employees Sumsel Babel Head Office with a proportionate stratified random sampling method with a sample size of 98 respondents in each division representing a total population of 3.362. This study uses multiple linear analysis techniques with a quantitative approach which shows the results that partially financial compensation and job satisfaction have a negative and significant effect on Employees of Bank Sumsel Babel Head Office. Keywords: Financial Compensation, Job Satisfaction, Turnover Keywords: Financial Compensation, Job Satisfaction, Turnover Intention